Exploring Ethical Business Practices In Sustainable Digital Marketing For MSMES - Ardi Armen; Taufan Herjanto (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2023)
This research aims to investigate ethical business practices in sustainable digital marketing among Micro, Small, and Medium Enterprises (MSMEs). The research model adopts a qualitative approach to delve into the intricacies of ethical decision-making processes within digital marketing strategies. Sampling techniques involve purposive sampling to select MSMEs known for their sustainable practices. Data analysis employs thematic analysis, allowing for the identification of patterns and themes related to ethical considerations in digital marketing. Preliminary findings indicate a growing consciousness among MSMEs towards adopting ethical principles in their digital marketing endeavors, contributing to the sustainability of their businesses while fostering consumer trust and loyalty. This study sheds light on the importance of ethical conduct in digital marketing for the long-term viability of MSMEs in the contemporary business landscape.